KAMPEN FOR OVERLEVELSE: Demografisk bevidsthed og forestillinger om forbundethed i den israelsk-jødiske - Goldberg, Helene (Tidsskriftet Antropologi, 2004)
To “be fruitful and multiply” is an imperative in Jewish law. Procreation has, therefore, a central place in Jewish religion and Jewish life. Since the state’s founding in 1948 the Israeli government has conducted a pronatalist policy to increase the Jewish population by encouraging Jewish childbirth and immigration to Israel. The country leads the world with the number of fertility clinics per capita, and treatments are heavily subsidized by the national health insurance. The explanation that is given for the scale of fertility clinics and the progressive fertility legislation national rests on the fear of losing the Jewish majority. The article problematizes this argument by exploring how demographic consciousness in Israel not only includes knowledge of the country’s demographic composition, but also collective memory of hardship, struggle and of origin. These issues answer the question as to who can be included in the national family. Central to demographic consciousness is kinship and gender, nationhood, Jewishness and citizenship. These notions of relatedness are made explicit and mobilized differently in changing situations of fertility treatments. The goal of the article is to show that insight into demographic consciousness is necessary to elucidate the complex context of fertility treatments in Israel.